Parameter dependencies of the experimental nitrogen concentration required for detachment on ASDEX Upgrade and JET. (September 2021) - Henderson, S.S.; Bernert, M.; Giroud, C.; Brida, D.; Cavedon, M.; David, P.; Dux, R.; Harrison, J.R.; Huber, A.; Kallenbach, A.; Karhunen, J.; Lomanowski, B.; et al.
Highlights: An experimental scaling law to predict the threshold nitrogen concentration required for detachment is presented based on spectroscopic measurements of N II emission. A least squares regression show that the threshold nitrogen concentration required for detachment depends strongly on the midplane separatrix density, with an exponent of −2.7 on AUG and −2.4 on JET, and approximately linearly with the power crossing the separatrix. These two parameter dependencies are consistent with measurements on both ASDEX Upgrade and JET. Equivalent predictions based on the well-known Lengyel model over-predict the absolute measured nitrogen concentration and show a weaker dependence on the separatrix density. Abstract: While current tokamak experiments are beginning to use real-time feedback control systems to manage the plasma exhaust, future tokamaks still require validation of theoretical models used to predict the threshold impurity concentration required to sufficiently reduce the power and particle fluxes to the divertor. This work exploits new spectroscopic measurements of the divertor nitrogen concentration, c N, in partially detached N2 -seeded H-mode plasmas on ASDEX Upgrade (AUG) and JET with the ITER-Like Wall (JET-ILW) to test the parameter dependencies of the power flowing to the outer divertor, P div, outer, and the separatrix electron density, n e, sep . A least-squares regression of the AUG measurements demonstrates that the threshold c N required for detachment scales as c N ∝ P div, outer 1.19 ± 0.32 n e, sep - 2.77 ± 0.36 . This scaling of n e, sep is also consistent with the measurements from JET which, at constant P div, outer, show c N ∝ n e, sep - 2.43 ± 0.27 . The dependencies of P div, outer and n e, sep is demonstrated over at least a factor of two change in both parameters and indicates a stronger dependence on n e, sep in comparison to the Lengyel model, which could be due to the assumption in this model that the heat flux channel width is independent of density. This first assessment of detachment scaling with impurity seeding highlights the need for further analysis of the systematic uncertainties of the measurement and more consistent scenarios from more tokamaks to investigate the machine size scaling.